Meningkatkan Keterampilan Menulis Teks Deskriptif Melalui Implementasi Model Pembelajaran Kooperatif "Make A Match" Menggunakan Media Kartu Gambar untuk Siswa Kelas V Sekolah dasar Negeri Curahsawo, Kabupaten Probolinggo - Nara Salsabila Aurellia; Ribut Prastiwi Sriwijayanti; Faridahtul Jannah (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This research was motivated by the low descriptive text writing skills of fifth-grade students at SD Negeri Curahsawo, Probolinggo Regency, where students faced obstacles in developing text structures, choosing proper diction, and organizing ideas systematically. This study aimed to determine the improvement of descriptive text writing skills through the implementation of the cooperative learning model type Make a Match assisted by picture card media. This study used Classroom Action Research (CAR) based on Kemmis and McTaggart's design, conducted in two cycles. Each cycle consisted of four main stages: planning, implementation, observation, and reflection. The subjects of this study were 14 fifth-grade students. Data were collected through observations, performance tests of writing, and documentation, then analyzed using quantitative and qualitative descriptive statistical analysis. In the initial pre-cycle phase, only 5 out of 14 students achieved mastery, with a low classical completeness of 35.71%. After the implementation of the actions, the results showed significant improvements. The class average score increased from 71.50 in cycle I to 83.21 in cycle II. The classical learning completeness also substantially increased from 42.86% in cycle I to 100% in cycle II, successfully exceeding the minimum indicator of 80%. In addition, students became more active, collaborative, and enthusiastic during the learning process. It concludes that the integration of the Make a Match model with visual media effectively optimizes students' descriptive writing skills in elementary schools.